Well, the commission should total $1,800. This is one tenth of what he sells, so he must sell $18,000 value of merchandise.
Let's pick two points on the line, the
y-intercept, and the
x-intercept. These are the points at which x=0, and y=0.
When x=0:
![y=-3/5x+6 \\y=-3/5(0)+6 \\y=6](https://tex.z-dn.net/?f=y%3D-3%2F5x%2B6%0A%5C%5Cy%3D-3%2F5%280%29%2B6%0A%5C%5Cy%3D6)
So one point is
(0,6)When y=0:
![y=-3/5x+6 \\0=-3/5x+6 \\-6=-3/5x \\-30=-3x \\x=10](https://tex.z-dn.net/?f=y%3D-3%2F5x%2B6%0A%5C%5C0%3D-3%2F5x%2B6%0A%5C%5C-6%3D-3%2F5x%0A%5C%5C-30%3D-3x%0A%5C%5Cx%3D10)
So another point is
(10,0)
So mark the points
(0,6) and
(10,0) on a pair of axes, and draw a straight line between them, and past them to infinity. This is a graphing of the line y=-3/5 x + 6
Answer:
46
Step-by-step explanation:
I would hAve say 2x23 which would have = to 46 that's what I got not sure if I'm correct
Answer:
a-![e^x,e^{-x}](https://tex.z-dn.net/?f=e%5Ex%2Ce%5E%7B-x%7D)
b-![x^{-2}](https://tex.z-dn.net/?f=x%5E%7B-2%7D)
c-![x^3](https://tex.z-dn.net/?f=x%5E3)
Step-by-step explanation:
a.7 y''-7 y =0
Auxillary equation
![D^2-1=0](https://tex.z-dn.net/?f=D%5E2-1%3D0)
![(D-1)(D+1)=0](https://tex.z-dn.net/?f=%28D-1%29%28D%2B1%29%3D0)
D=1,-1
Then , the solution of given differential equation
![y=e^x,y=e^{-x}](https://tex.z-dn.net/?f=y%3De%5Ex%2Cy%3De%5E%7B-x%7D)
2.![7x^2y''+14xy'-14 y=0](https://tex.z-dn.net/?f=7x%5E2y%27%27%2B14xy%27-14%20y%3D0)
Y=![y=x^3](https://tex.z-dn.net/?f=y%3Dx%5E3)
![y=3x^2](https://tex.z-dn.net/?f=y%3D3x%5E2)
![y''=6x](https://tex.z-dn.net/?f=y%27%27%3D6x)
Substitute in the given differential equation
![42x^3+42x^3-14x^3\neq 0](https://tex.z-dn.net/?f=42x%5E3%2B42x%5E3-14x%5E3%5Cneq%200)
Hence,
is not a solution of given differential equation
are also not a solution of given differential equation.
y=![x^{-2}](https://tex.z-dn.net/?f=x%5E%7B-2%7D)
![y'=-2x^{-3}](https://tex.z-dn.net/?f=y%27%3D-2x%5E%7B-3%7D)
![y''=6x^{-4}](https://tex.z-dn.net/?f=y%27%27%3D6x%5E%7B-4%7D)
Substitute the values in the differential equation
![7x^2(6x^{-4})+14x(-2x^{-3})-14 x^{-2}](https://tex.z-dn.net/?f=7x%5E2%286x%5E%7B-4%7D%29%2B14x%28-2x%5E%7B-3%7D%29-14%20x%5E%7B-2%7D)
=![42x^{-2}-28x^{-2}-14x^{-2}=0](https://tex.z-dn.net/?f=42x%5E%7B-2%7D-28x%5E%7B-2%7D-14x%5E%7B-2%7D%3D0)
Hence,
is a solution of given differential equation.
c.![7x^2y''-42y=0](https://tex.z-dn.net/?f=7x%5E2y%27%27-42y%3D0)
![y=x^3](https://tex.z-dn.net/?f=y%3Dx%5E3)
![y'=3x^2](https://tex.z-dn.net/?f=y%27%3D3x%5E2)
![y''=6x](https://tex.z-dn.net/?f=y%27%27%3D6x)
Substitute the values in the differential equation
![42x^3-42x^3=0](https://tex.z-dn.net/?f=42x%5E3-42x%5E3%3D0)
Hence,
is a solution of given differential equation.
a-![e^x,e^{-x}](https://tex.z-dn.net/?f=e%5Ex%2Ce%5E%7B-x%7D)
b-![x^{-2}](https://tex.z-dn.net/?f=x%5E%7B-2%7D)
c-![x^3](https://tex.z-dn.net/?f=x%5E3)